Clinical epidemiology of orthopaedic trauma - Zhang, Yingze (Thieme, 2021)
Unique resource provides foundation for worldwide prevention, diagnosis, and treatment of orthopaedic fractures Clinical Epidemiology of Orthopaedic Trauma, Third Edition by renowned orthopaedic surgeon and researcher Yingze Zhang and an impressive cadre of contributors expands on the widely acclaimed prior editions. Leveraging an epidemiological database with the distinction of being the largest domestic and foreign sample volume of orthopaedic trauma, this remarkable book expands on the epidemiology of fractures in China, with national incidence rates new to this edition. It offers a wealth